Logistics of Intellectual Property - Čovo, Petar; Maruna, Marko (Oeconomica Jadertina, 2017)
In a business world where there is great competition between companies seeking to find solutions to surmount the difficulties they face. One of the ways they do that is the development of logistics and innovation. Companies often find solutions, it is innovation that want to overtake the competition and generate substantial revenue for the competition before it manages to find out. Numerous innovations over time and become a patent by which the company can be recognized. Logistics task is to connect business processes from concept to finished product to market. In Croatia, the state of patents is not growing strongly, but on the contrary is declining. For the procedure for the protection and realization of rights in the Republic in charge of the State Intellectual Property Office, which takes care of the above application and presents the results in their annual reports.
Keywords: logistics; intellectual property; innovation; knowledge